Cryptochrome-Related Abiotic Stress Responses in Plants - D’Amico-Damião, Victor; Carvalho, Rogério Falleiros (Frontiers in Plant Science, 2018)
It is well known that light is a crucial environmental factor that has a fundamental role in plant growth and development from seed germination to fruiting. For this process, plants contain versatile and multifaceted photoreceptor systems to sense variations in the light spectrum and to acclimate to a range of ambient conditions. Five main groups of photoreceptors have been found in higher plants, cryptochromes, phototropins, UVR8, zeitlupes and phytochromes, but the last one is the most characterized and widely studied class of photoreceptors for red/far red wavelengths. Among the many responses modulated by phytochromes, these molecules play an important role in biotic and abiotic stress responses, which is one of the most active research topics in plant biology, especially their effect on agronomic traits. However, regarding the light spectrum, it is not surprising to consider that other photoreceptors are also part of the stress response modulated by light. In fact, it has become increasingly evident that cryptochromes, which mainly absorb in the blue light region, also act as key regulators of a range of plant stress responses, such as resistance to pathogens, osmotic stress, and high salinity. However, this information is commonly excluded from many kinds of research articles. Therefore, for the first time in the literature, the scope of the present review is to compile and discuss the evidence on the abiotic stress responses in plants that are modulated by cryptochromes.